Benthic oxygen dynamics and implication for the maintenance of chronic hypoxia and ecosystem degradation in the Berre lagoon (France). (5th September 2021) - Rigaud, Sylvain; Deflandre, Bruno; Grenz, Christian; Cesbron, Florian; Pozzato, Lara; Voltz, Baptiste; Grémare, Antoine; Romero-Ramirez, Alicia; Mirleau, Pascal; Meulé, Samuel; Faure, Vincent; Mayot, Nicolas; et al.
Abstract: Chronic hypoxia and anoxia have strong impacts on coastal ecosystems worldwide. In shallow coastal ecosystems, such situations are essentially driven by high benthic oxygen (O2 ) demand resulting from organic matter mineralization in surface sediment and amplified by a low mixing of the water column. However, the benthic O2 demand may greatly vary according to the O2 availability, sediment biogeochemical properties, and bioturbation by macrobenthic fauna. Here we examined how the sediment O2 demand varies in response to seasonal and long-lasting (pluri-decadal) hypoxia in the Berre lagoon, a coastal ecosystem impacted by chronic hypoxia events since 60 years. Oxygen penetration depth, diffusive and total O2 fluxes were measured in situ using a microelectrode autonomous profiler and benthic chamber deployments at three sites impacted by quite-permanent (PA), seasonal (PI) and occasional (PO) hypoxia in August 2016. They were seasonally repeated at site PI between August 2015 and August 2016. Additional physical and chemical characteristics were also measured in surface sediment. Sediment profile images and characteristics of benthic macrofauna communities enabled to estimate the quality of the benthic ecosystem. The highest benthic O2 demand was observed after seasonal anoxia in relation to the important accumulation of reduced chemical species in surface sediment. Interestingly, both pluri-decadal hypoxia and normoxia produced relatively high benthic O2 demand related to a higher accumulation of organic matter and to the presence of reduced chemical species at site dominated by hypoxia, and to the presence of fresher organic matter and active bioturbating macrofaunal communities in normoxic site. The low benthic O2 demand at site seasonally impacted by hypoxia likely resulted from the degraded state of the macrofaunal community and from the lower accumulation of reduced chemical species. The occurrence of hypoxia and anoxia situations in the Berre lagoon was predicted from the competition between kinetics of benthic O2 demand and water column reoxygenation events induced by strong wind. The good agreement between the measured and predicted hypoxia/anoxia occurrence clearly indicates that the chronic deoxygenation events in the Berre lagoon, and the resulting degraded ecological state of the benthic ecosystem are driven both by the benthic O2 demand and by the intensity and duration of the water column stratification. Highlights: The benthic oxygen demand (BOD) varies with seasonal and long-lasting deoxygenation events. BOD is firstly driven by oxygen availability in the water column. Hypoxia generates highest BOD for the oxidation of accumulated reduced chemical species. Long-lasting normoxia generates high BOD because of high bioturbation and fresher organic matter. BOD and water column stratification are responsible of the chronic deoxygenation in the Berre lagoon.